How to support students and the learning process during India’s COVID-19 school closures - Pant, Anjali; Scott, Samuel P.; Nguyen, Phuong Hong (International Food Policy Research Institute, 2022)
The COVID-19 pandemic has affected 1.6 billion learners worldwide, and school closures could lead to a loss of 0.3–0.9 years of schooling, according to World Bank estimates; a global shutdown of five months could result in lost earnings of $10 trillion over students’ lifetimes. The pandemic’s economic shocks are likely to increase school drop-out rates. Evidence suggests that the poor, girls, and other marginalized groups disproportionately suffer the consequences of school closures.